PENGELOLAAN KEUANGAN UKM BATIK DI KOTA MALANG - Rahadjeng, Erna Retno (IQTISHODUNA, 2015)
Batik Malang commonly called by Batik Malangan is not yet as popular as Batik Jawa. Batik Malangis very beautiful batik as it has a distinctive and uniqueness among the other batik. Issues examined in thisresearch are: How is the Financial Management of UKM Batik in Malang? What are the factors used inFinancial Management of UKM Batik in Malang? The method used in this research is descriptive. Thepurpose of this descriptive research is to make a systematic overview description, factual and accurate as wellas to explain and to analyze and then draw a conclusion from the results of research on the efforts of financialmanagement and financial performance of UKM. Based on the analysis above shows that batik in Malangwhich consists of three batik ownersthey are not optimal in managing their business finances. The reportingthat is made so far is just a very basic report which only consists of income and expense of funds reportwithout any further action.For good financial management, the necessary steps to be done areto make financialplanning, financial budgeting, financial management and control. If the measure of financial management isdone correctly it will increase the financial performance of batik entrepreneurs in Malang.